Association of antenatal magnesium sulfate with reduced late-onset sepsis in extreme preterm infants. Issue 1 (2nd January 2023) - Vanhaesebrouck, Sophie; Zecic, Alexandra; Goossens, Linde; Keymeulen, Annelies; Garabedian, Lara; De Meulemeester, Julie; Naessens, Pauline; De Coen, Kris; Smets, Koenraad
ABSTRACT: Objectives: Neonatal intensive care has changed extensively over the last decades resulting in improved survival of extreme preterm infants. However, improved survival is associated with prolonged hospitalization, mechanical ventilation and use of invasive devices, which are all predisposing factors for LOS. LOS is known to increase short- and long-term morbidities resulting in impaired neurodevelopmental outcome. Besides treatment with antibiotics and supportive care, there is an unmet need for adjunctive therapies to prevent neonatal sepsis and hereby improve outcome. Methods: In a retrospective single-center design, we explored underlying pre-, peri- and postnatal factors in extreme preterm infants with and without LOS to potentially identify future strategies in the prevention of LOS in these infants. Results: Associations formerly published could be confirmed, such as lower birth weight, longer duration of respiratory support, parenteral nutrition and NICU stay and a higher incidence of almost all neonatal morbidities. A new interesting finding was the fact that infants with LOS received more antenatal magnesium sulfate (p = 0.002). After nearest neighbor matching based on birth weight, gestational age, gender and multiplicity increased duration of parenteral nutrition and NICU stay, the incidence of PVL remained significantly different between the two groups (LOS/no LOS), but also the association between antenatal magnesium sulfate administration and less LOS held true (p = 0.004). Conclusion: In this study, extreme preterm infants receiving antenatal magnesium sulfate developed less LOS. Whether this is merely an associative factor reflecting illness severity or an interesting link for new preventive strategies for LOS, should be further explored.